Semiconducting Tin and Lead Iodide Perovskites with Organic Cations: Phase Transitions, High Mobilities, and Near-Infrared Photoluminescent Properties - Stoumpos, Constantinos C; Malliakas, Christos D; Kanatzidis, Mercouri G (Inorganic chemistry, 2013)
A broad organic–inorganic series of hybrid metal iodide perovskites with the general formulation AMI3, where A is the methylammonium (CH3NH3 +) or formamidinium (HC(NH2)2 +) cation and M is Sn (1 and 2) or Pb (3 and 4) are reported. The compounds have been prepared through a variety of synthetic approaches, and the nature of the resulting materials is discussed in terms of their thermal stability and optical and electronic properties. We find that the chemical and physical properties of these materials strongly depend on the preparation method. Single crystal X-ray diffraction analysis of 1–4 classifies the compounds in the perovskite structural family. Structural phase transitions were observed and investigated by temperature-dependent single crystal X-ray diffraction in the 100–400 K range. The charge transport properties of the materials are discussed in conjunction with diffuse reflectance studies in the mid-IR region that display characteristic absorption features. Temperature-dependent studies show a strong dependence of the resistivity as a function of the crystal structure. Optical absorption measurements indicate that 1–4 behave as direct-gap semiconductors with energy band gaps distributed in the range of 1.25–1.75 eV. The compounds exhibit an intense near-IR photoluminescence (PL) emission in the 700–1000 nm range (1.1–1.7 eV) at room temperature. We show that solid solutions between the Sn and Pb compounds are readily accessible throughout the composition range. The optical properties such as energy band gap, emission intensity, and wavelength can be readily controlled as we show for the isostructural series of solid solutions CH3NH3Sn1–x Pb x I3 (5). The charge transport type in these materials was characterized by Seebeck coefficient and Hall-effect measurements. The compounds behave as p- or n-type semiconductors depending on the preparation method. The samples with the lowest carrier concentration are prepared from solution and are n-type; p-type samples can be obtained through solid state reactions exposed in air in a controllable manner. In the case of Sn compounds, there is a facile tendency toward oxidation which causes the materials to be doped with Sn4+ and thus behave as p-type semiconductors displaying metal-like conductivity. The compounds appear to possess very high estimated electron and hole mobilities that exceed 2000 cm2/(V s) and 300 cm2/(V s), respectively, as shown in the case of CH3NH3SnI3 (1). We also compare the properties of the title hybrid materials with those of the “all-inorganic” CsSnI3 and CsPbI3 prepared using identical synthetic methods.